Substitution of Chemical Fertilizer Using Natural Hormone and Cow Biourine On Growth and Yield of Shallot (Allium Cepa L.) - Lagiman; Nugraha, Ihvan Mei; Suryawati, Ami; Sutoto, Supono Budi (Proceeding International Conference on Science and Engineering, 2020)
The use of natural hormone of sprout extract, coconut water, and banana stem extract and application of cow biourine has been introduced as an innovation to reduce the use of chemical fertilizers to increase the productivity of shallot. This study aims to compare the growth and yield of shallot with chemical fertilizer treatment and that of shallot treated with combination of natural hormone and cow biourine. The study was conducted in Temon Wetan, Temon, Kulon Progo, Special Region of Yogyakarta using a Complete Randomized Block Design, which consists of two factors and one control (chemical fertilizer). The first factor is a natural hormone: sprout extract, banana stem extract and coconut water. The second factor is the concentration of cow biourine: 30%, 40%, and 50%. Data were analyzed using diversity at 5% level, Orthogonal Contras at 5% level and DMRT Test with 5% level. It was revealed that the control group with a combined treatments was not significantly different from the growth and yield of shallot of the group with chemical fertilizers. Types of treatments with natural hormone and cow biourine concentrations provided the same growth and yield as that of chemical fertilizer.